Movement Characteristics and Ultrastructural Studies of Fresh and Acrosome-Reacted Jermasia Goat Sperm - N.H, Hashida; R.B, Abdullah (Malaysian Journal of Science, 2005)
The present studies were undertaken to investigate the effects of acrosome reaction on the movement characteristics and ultrastructure of Jermasia goat sperm. The semen was subjected to acrosome reaction prior to Transmission Electron Microscopic (TEM) procedures and evaluated for sperm movement characteristics with automated semen analyzer (IVOS). Generally, total motility (TM), progressive motility (PM), rapid motility (RM), medium motility (MM), slow motility (SM) and static of the acrosome-reacted sperm were significantly lower and VAP (average path velocity), VSL (straight line velocity), VCL (curvilinear velocity), ALH (amplitude of lateral head displacement), BCF (beat cross frequency), STR (straightness) and LIN (linearity) were significantly higher than the fresh sperm (P≤0.05). Ultrastuctural study of the acrosome-reacted sperm showed that the acrosomal and plasma membrane were ruptured, with dispersion of the acrosomal matrix. The acrosome-reacted sperm midpiece showed the disruption of plasma membrane, elongated shape of the mitochondria and irregular shape of the nine outer dense fibres.